Evaluation of Sector 6 Citarum Harum's Social Media for Waste Management - Pertiwi, Annisa Bela; Farid, Rudy; Budiman; Benyamin, M Firdaus; Rinaldi, Mario (Mediator: Jurnal Komunikasi, 2024)
The study aims to analyze the utilization of information media platforms by the Citarum Harum Task Force Sector 6 in waste management endeavors within the Baleendah District, Bandung Regency. The platforms under scrutiny include Instagram (@guardian_sektor6), YouTube (guardian_citarum), and TikTok (guardian_citarum). Employing a qualitative approach, the study integrates interviews, direct observations, and document analysis. Findings underscore the imperative of developing an official website to enhance information dissemination and organization. Notably, while the Instagram account @guardian_sektor6 demonstrates consistent posting and visually appealing content, shortcomings include inconsistent hashtag usage and limited content diversity. Similarly, the YouTube channel guardian_citarum maintains posting consistency but lacks optimization in SEO utilization and incomplete video descriptions. Meanwhile, TikTok account guardian_citarum, though active and visually engaging, underutilizes features such as hashtags and User-Generated Content. Consequently, the research output comprises a wireframe layout design for the official website of the Citarum Harum Task Force Sector 6. It is envisaged that this wireframe design will amplify the effectiveness of information delivery and waste management socialization efforts in the areas overseen by the Citarum Harum Task Force Sector 6.